Small-particle-size mo-v-based catalysts, methods of making, and uses thereof

CN122912869APending Publication Date: 2026-10-16새틀라이트뉴머티리얼즈알앤디컴퍼니리미티드 +1
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202611425368.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-15
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0007]针对现有丙烯醛氧化制丙烯酸催化剂制备技术中存在反应过程中用水量大(50-90wt%)造成后续除水能耗高、耗时长、干燥过程水热副反应剧烈、催化剂批次间稳定性差的问题,本发明提供了一种利用湿式球磨法制备的Mo-V基催化剂的方法

Benefits of technology

[0029]1. This invention utilizes wet ball milling to significantly reduce the water consumption in the reaction process by up to 99%, shortens the reaction time, effectively reduces the reaction energy consumption of the Mo-V-based catalyst for the oxidation of acrolein to acrylic acid, avoids hydrothermal side reactions during the drying process, improves the batch-to-batch stability of the catalyst synthesis, and the preparation process is environmentally friendly and produces no waste gas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912869A_ABST
    Figure CN122912869A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of catalyst preparation, in particular to a small-particle-size Mo-V-based catalyst prepared by a wet ball milling method, a preparation method and application. The application greatly reduces the water consumption in the reaction process by 99% by using the wet ball milling method, shortens the reaction time, effectively reduces the reaction energy consumption of the Mo-V-based catalyst for propylene aldehyde oxidation to prepare propylene acid, avoids the hydrothermal side reaction in the drying process, improves the batch-to-batch stability of catalyst synthesis, and is environment-friendly and free of waste gas in the preparation process. The prepared catalyst has the characteristics of small particle size and high exposure of active centers, meanwhile, the introduction of the pore-forming agent improves the specific surface area of the catalyst, enriches the pore structure, and inhibits the production of by-products, so that the catalyst has high propylene acid selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of catalyst preparation technology, specifically to small-particle-size Mo-V-based catalysts prepared by wet ball milling, preparation methods, and applications. Background Technology

[0002] Acrylic acid, as an important chemical raw material, is used in polymers / copolymers prepared by copolymerizing it / its esters with other monomers. These polymers / copolymers are widely used in many industries such as coatings, textiles, chemical fibers, adhesives, leather, detergents, papermaking, plastics, rubber, medical, and oilfield chemicals. They have penetrated into various fields of daily life and high-tech materials in the national economy and have a broad market space.

[0003] Currently, there are several routes for synthesizing acrylic acid, including the cyanoethanol method, acetylene carbonylation method, two-step propylene oxidation method, direct propane oxidation method, lactic acid dehydration method, glycerol oxidation method, and aldol condensation method. Among these, the two-step propylene oxidation method is the main method for producing acrylic acid. In this method, propylene is first converted to acrolein under oxygen-containing conditions, and then oxygen is added to further convert acrolein to acrylic acid. The catalyst used in the second step is primarily a molybdenum (Mo)-vanadium (V) oxide-based catalyst system. Compared to the one-step method, the two-step method, although more complex, offers higher yields and significantly reduces raw material separation costs. In the two-step reaction, the effective yield of the first step is approximately 92%, while the yield of acrylic acid in the second step can reach 90%.

[0004] Existing technologies include modified catalyst systems based on Mo-V oxides applied to the oxidation of acrolein to acrylic acid, aiming to improve the conversion rate of acrolein and the yield of acrylic acid. For example, Nippon Shokubai Chemical (patent numbers CN1031488A, CN101328116B, CN101274279B) disclosed a method for preparing a catalyst for the oxidation of acrolein to acrylic acid. A Mo-VW-Cu composite metal oxide catalyst was prepared in a system with a water content of nearly 85%, achieving an acrolein conversion rate of 85.3-99.8% and an acrylic acid yield of 72.5-97.5%. BASF (patent number CN1083734C) disclosed a Mo-V-based catalyst with a copper-containing wolframite structure, achieving an acrylic acid selectivity of over 96% at a 99% acrolein conversion rate. This catalyst was prepared with a water content of 86.7%. Mitsubishi Chemical (patent number CN1697703A) disclosed a Mo-Nb-V-Sb composite oxide catalyst system incorporating Cu and Si-C components, achieving an acrolein conversion rate of 99.0%, an acrylic acid selectivity of 98.5%, and an acrylic acid yield of 97.5%. The catalyst preparation process contained 53.7% water. Nippon Kayaku (patent number WO2013084500A3) disclosed a Mo-VW-Cu-Sb multi-component composite metal oxide catalyst, which improved catalyst strength and wear resistance through spray drying and two-step calcination. This catalyst achieved an acrolein conversion rate of 98.9%, an acrylic acid selectivity of 97.6%, and an acrylic acid yield of 96.6%. The catalyst preparation process contained 80.6% water. China National Petroleum Corporation (patent numbers CN1445020A and CN1169619C) disclosed a method that introduces tellurium (Te) as a key stabilizer into a Mo-V-Cu composite oxide catalyst system, optimizing the interaction and dispersibility among the components. This method achieves an acrolein conversion rate of up to 99.5% and an acrylic acid selectivity of up to 98.7%, with a water content of 52.4% during catalyst preparation. CNOOC Tianjin Chemical Research and Design Institute (patent numbers CN114887627B and CN102039143B) prepared a catalyst precursor using a water / organic phase mixture system. Combining distillation dehydration, spray drying, and optimized coating processes, they obtained a Mo-V-Cu-W-Sb composite oxide catalyst with high specific surface area, high loading capacity, and high thermal stability. This catalyst achieved an acrolein conversion rate of 98.8%, an acrylic acid selectivity of 98.7%, and an acrylic acid yield of 97.5%, with a water content of 76.3% during catalyst preparation.Shanghai Huayi New Materials Co., Ltd., with patent numbers (EP4547641A1, CN106881101B, CN104646014B, CN102114427B), discloses a Mo-V-Cu-W-Si based composite oxide catalyst prepared by activation pretreatment, with an acrolein conversion rate of 99.5% and an acrylic acid yield of 97.3%. The catalyst preparation process contains 74.5% water. China Petroleum & Chemical Corporation (patent number CN103877987B) has prepared VMo3O through pretreatment. 11 Powder is used as the active phase, and then mixed with other components to obtain a Mo-V-Cu-W-Sb-based composite oxide catalyst, which solves the problem of insufficient activity and selectivity of traditional catalysts. At the same time, combined with optimized preparation process and molding technology, the industrial application of high-performance acrylic acid catalyst is realized. It can still maintain an acrolein conversion rate of more than 99% and an acrylic acid selectivity of more than 94% during long-term operation. The water content of the catalyst during preparation is 84.7%.

[0005] Although the aforementioned invention patents have improved the stability, activity, or acrylic acid yield of Mo-V-based catalysts for the oxidation of acrolein to acrylic acid through methods such as additive addition, structural modification, introduction of stabilizers, optimization of dehydration processes, pretreatment of active components, and pre-preparation of active phases, the water consumption in the preparation process accounts for more than 50% of the catalyst synthesis process, reaching as high as 86.7%. The introduction of large amounts of water into the reaction system leads to drawbacks such as high energy consumption for subsequent drying, vigorous hydrothermal reactions increasing side reactions or reducing batch stability, and high levels of contamination.

[0006] Therefore, a method for providing an efficient catalyst for the synthesis of acrolein to acrylic acid with low water consumption is provided, which helps to reduce the production cost of the catalyst and improve the economic efficiency of acrylic acid plants. Summary of the Invention

[0007] To address the problems in existing catalyst preparation technologies for the oxidation of acrolein to acrylic acid, such as high water consumption (50-90 wt%) leading to high energy consumption and long processing time in subsequent dehydration, severe hydrothermal side reactions during drying, and poor batch-to-batch catalyst stability, this invention provides a method for preparing Mo-V-based catalysts using wet ball milling. This method significantly reduces water consumption (1-15 wt%) during catalyst synthesis, lowering energy consumption and reaction time. Simultaneously, the substantial reduction in water consumption avoids hydrothermal side reactions during drying, improving batch-to-batch catalyst stability. Furthermore, the small particle size of the catalyst prepared by ball milling ensures sufficient exposure of effective active sites, contributing to improved acrylic acid selectivity.

[0008] To achieve the above objectives, the first aspect of the present invention provides a method for preparing small-particle-size Mo-V-based catalysts using a wet ball milling method, comprising the following steps:

[0009] (1) Place the raw materials containing Mo, V, W, Cu, and Sb and the pore-forming agent into a mixer, mix them, and then transfer them to a ball mill jar to obtain a mixture;

[0010] (2) Add lubricant and water to the mixture; the amount of water added is 1-15 wt% of the total mass of the raw materials containing Mo, V, W, Cu, and Sb.

[0011] (3) At normal temperature and pressure, the ball mill jar is used to ball mill for 10-40 min at a rate of 150-400 rpm / min;

[0012] (4) After ball milling, the mixture is dried in an oven to obtain the catalyst precursor;

[0013] (5) The catalyst precursor was placed in a tube furnace and calcined to obtain a small particle size Mo-V-based catalyst.

[0014] In some preferred embodiments, the Mo-containing raw material is selected from at least one of ammonium molybdate and molybdenum trioxide;

[0015] The raw material containing V is selected from at least one of vanadium oxalate, ammonium metavanadate, and vanadium pentoxide;

[0016] The raw material containing W is selected from at least one of ammonium tungstate, ammonium paratungstate, ammonium metatungstate, and tungsten trioxide;

[0017] The raw materials containing Cu are selected from at least one of copper carbonate, copper nitrate, copper sulfate, basic copper sulfate, copper acetate, copper oxalate, copper phosphate, and copper oxide.

[0018] The raw materials containing Sb are selected from at least one of antimony acetate and antimony oxide.

[0019] In some preferred embodiments, the pore-forming agent is selected from at least one of carboxymethyl cellulose, hydroxyethyl cellulose polyoxyethylene polyoxypropylene ether block copolymer (F127), polyethylene oxide-polyoxypropylene-polyoxyethylene triblock copolymer (P123), and polyethylene glycol, and its addition amount is 2 to 10 wt% of the total mass of raw materials containing Mo, V, W, Cu, and Sb.

[0020] In some preferred embodiments, the lubricant is selected from at least one of glycerol, ethanolamine, and ethylene glycol, and its addition amount is 0 to 5 wt% of the total mass of raw materials containing Mo, V, W, Cu, and Sb.

[0021] In some preferred embodiments, the ball mill jar is used to ball mill for 15-30 minutes at a speed of 200-300 rpm / min.

[0022] In some preferred embodiments, the air feed rate of the tubular furnace is 10-40 mL / min, and the heating rate is 2-4 °C / min.

[0023] In some preferred embodiments, the calcination temperature is 330~410°C and the time is 8~12 hours.

[0024] The wet ball milling method for preparing small-particle-size Mo-V-based catalysts provided by this invention relies on the synergistic effect of mechanochemistry and liquid-phase interface reaction: the mechanical impact and shear force of the grinding balls breaks down Mo, V, and other metal raw materials to the nanoscale, inducing lattice distortion and generating a large number of defects and strain energy to activate the powder; the liquid medium both inhibits the hard agglomeration of ultrafine particles and achieves highly uniform dispersion of metal ions through the solvation layer, and promotes chemical interactions between ions in the liquid-phase interface layer; the synergistic effect of these two processes allows the raw materials to generate a highly active precursor of M1 crystal phase combined with M2 crystal phase at low temperature, and then obtains a Mo-V-based composite oxide catalyst with smaller grains and sufficient exposure of the active phase through drying and calcination. Compared with dry ball milling, this method effectively avoids elemental segregation and the formation of inert impurities. Simultaneously, the core of this invention is to reduce the water consumption in the catalyst synthesis process. When the water content exceeds 15%, it will increase energy consumption. Therefore, an appropriate water content ensures both reduced energy consumption in catalyst preparation and does not affect the formation of its active phase.

[0025] The second aspect of this invention provides a small-particle-size Mo-V-based catalyst prepared by wet ball milling, obtained by the above method, and having the general formula Mo. 12 V a W b Cu c Sb d O x In the formula, a, b, c, and d represent the atomic ratios of each element, where a = 1~5, b = 0.5~2.5, c = 0.5~3, and d = 0~1.5.

[0026] In some preferred embodiments, the catalyst has a particle size D50 of 0.46-0.64 μm, a D90 of 10.20-13.56 μm, and a specific surface area of ​​7.01-8.99 m². 2 / g.

[0027] The third aspect of this invention provides an application of a small-particle-size Mo-V-based catalyst prepared by wet ball milling, used in the catalytic oxidation of acrolein to prepare acrylic acid.

[0028] Compared with existing technologies, the beneficial effects are as follows:

[0029] 1. This invention utilizes wet ball milling to significantly reduce the water consumption in the reaction process by up to 99%, shortens the reaction time, effectively reduces the reaction energy consumption of the Mo-V-based catalyst for the oxidation of acrolein to acrylic acid, avoids hydrothermal side reactions during the drying process, improves the batch-to-batch stability of the catalyst synthesis, and the preparation process is environmentally friendly and produces no waste gas.

[0030] 2. The catalyst prepared by ball milling in this invention has the characteristics of small particle size and more exposed active centers. At the same time, the introduction of pore-forming agent increases the specific surface area of ​​the catalyst, enriches the pore structure, and inhibits the production of by-products, so that the catalyst has high acrylic acid selectivity. Attached Figure Description

[0031] Figure 1 The XRD patterns are of the catalysts synthesized in Example 1, Comparative Example 3, and Comparative Example 7.

[0032] Figure 2 The XRD patterns are of the catalysts synthesized in Example 1 and Comparative Examples 4-6.

[0033] Figure 3 The image shows a SEM image of the catalyst prepared in Example 1.

[0034] Figure 4 The image shows a SEM image of the catalyst prepared in Comparative Example 3.

[0035] Figure 5 The image shows a SEM image of the catalyst prepared in Comparative Example 7.

[0036] Figure 6 This is a SEM mapping image of the catalyst in Example 1. Detailed Implementation

[0037] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0038] Unless otherwise specified in the examples and comparative examples, the conditions were performed under standard conditions or conditions recommended by the manufacturer. All reagents and instruments used were commercially available products unless otherwise specified.

[0039] Example 1: Mo 12 V4W 2.2 Cu2Sb 0.8 O x Preparation of -5wt%H2O (STL-BM-5W)

[0040] A method for preparing small-particle-size Mo-V-based catalysts using wet ball milling includes the following steps:

[0041] S1. Weigh out 55.0 g ammonium molybdate, 12.15 g ammonium metavanadate, 14.07 g ammonium metatungstate, 12.54 g copper nitrate and 6.21 g antimony acetate in sequence and add them to a conical mixer. Stir at 15 rpm / min for 10 min and then add 5.0 g hydroxyethyl cellulose. Continue stirring for 10 min.

[0042] S2. After mixing, transfer the mixture to a ball mill, add 5.0 g of water and 2.0 g of glycerol in sequence, and ball mill at 250 rpm / min for 20 min;

[0043] S3. After ball milling, dry in an oven at 80℃ for 2 h to obtain the catalyst precursor;

[0044] S4. The catalyst precursor was placed in a tube furnace and calcined at 390°C for 9 h under air atmosphere at a rate of 3°C / min to obtain catalyst powder. The general formula for the proportions of its elements is Mo. 12 V4W 2.2 Cu2Sb 0.8 O x It is denoted as STL-BM-5W. Its XRD pattern, SEM image, and SEM mapping image are shown below. Figures 1-3 and Figure 6 As shown.

[0045] Example 2: Mo 12 V4W 2.2 Cu2Sb 0.8 O x Preparation of -1wt%H2O (STL-BM-1W)

[0046] A method for preparing small-particle-size Mo-V-based catalysts using wet ball milling includes the following steps:

[0047] S1. Weigh out 55.0 g ammonium molybdate, 12.15 g ammonium metavanadate, 14.07 g ammonium metatungstate, 12.54 g copper nitrate and 6.21 g antimony acetate in sequence and add them to a conical mixer. Stir at 15 rpm / min for 10 min and then add 7.0 g hydroxyethyl cellulose. Continue stirring for 10 min.

[0048] S2. After mixing, transfer the mixture to a ball mill, add 1.0 g of water and 1.0 g of glycerol in sequence, and ball mill at 220 rpm / min for 15 min;

[0049] S3. After ball milling, dry in an oven at 80℃ for 2 h to obtain the catalyst precursor;

[0050] S4. The catalyst precursor was placed in a tube furnace and calcined at 400°C for 9 h under air atmosphere at a rate of 5°C / min to obtain catalyst powder. The general formula for the proportions of its elements is Mo. 12 V4W 2.2 Cu2Sb 0.8 O x It is denoted as STL-BM-1W.

[0051] Example 3: Mo 12 V4W 2.2 Cu2Sb 0.8 O x Preparation of -10wt%H2O (STL-BM-10W)

[0052] A method for preparing small-particle-size Mo-V-based catalysts using wet ball milling includes the following steps:

[0053] S1. Weigh out 55.0 g ammonium molybdate, 16.09 g vanadium oxalate, 14.07 g ammonium metatungstate, 12.54 g copper nitrate and 6.21 g antimony acetate in sequence and add them to a conical mixer. Stir at 10 rpm / min for 10 min and then add 5.20 g F127. Continue stirring for 8 min.

[0054] S2. After mixing, transfer the mixture to a ball mill, add 10.39 g of water and 2.08 g of glycerol in sequence, and ball mill at 300 rpm / min for 15 min;

[0055] S3. After ball milling, dry in an oven at 90℃ for 2 h to obtain the catalyst precursor;

[0056] S4. The catalyst precursor was placed in a tube furnace and calcined at 380°C for 9 h under air atmosphere at a rate of 4°C / min to obtain catalyst powder. The general formula for the proportions of its elements is Mo. 12 V4W 2.2 Cu2Sb 0.8 O x It is denoted as STL-BM-10W.

[0057] Example 4: Mo 12 V4W 2.2 Cu2Sb 0.8 O x Preparation of -15wt%H2O (STL-BM-15W)

[0058] A method for preparing small-particle-size Mo-V-based catalysts using wet ball milling includes the following steps:

[0059] S1. Weigh out 55.0 g ammonium molybdate, 12.15 g ammonium metavanadate, 14.07 g ammonium metatungstate, 10.37 g copper acetate and 6.21 g antimony acetate in sequence and add them to a conical mixer. Stir at 15 rpm / min for 8 min and then add 4.89 g P123. Continue stirring for 10 min.

[0060] S2. After mixing, transfer the mixture to a ball mill, add 14.67 g of water and 2.93 g of glycerol in sequence, and ball mill at 200 rpm / min for 18 min;

[0061] S3. After ball milling, dry in an oven at 80℃ for 3 h to obtain the catalyst precursor;

[0062] S4. The catalyst precursor was placed in a tube furnace and calcined at 390°C for 9 hours under air atmosphere at a rate of 5°C / min to obtain catalyst powder. The general formula for the proportions of its elements is Mo. 12 V4W 2.2 Cu2Sb 0.8 O x It is denoted as STL-BM-15W.

[0063] Example 5: Mo 12 V 4.4 W 1.8 Cu 1.5 Sb 1.3 O x Preparation of -5wt%H2O (STL-BM-5W-2)

[0064] A method for preparing small-particle-size Mo-V-based catalysts using wet ball milling includes the following steps:

[0065] S1. Weigh out 55.0 g ammonium molybdate, 13.36 g ammonium metavanadate, 11.51 g ammonium metatungstate, 9.41 g copper nitrate and 10.09 g antimony acetate in sequence and add them to a conical mixer. Stir at 15 rpm / min for 10 min and then add 4.97 g polyethylene glycol and continue stirring for 10 min.

[0066] S2. After mixing, transfer the mixture to a ball mill, add 4.97 g of water and 1.99 g of glycerol in sequence, and ball mill at 250 rpm / min for 20 min;

[0067] S3. After ball milling, dry in an oven at 80℃ for 2 h to obtain the catalyst precursor;

[0068] S4. The catalyst precursor was placed in a tube furnace and calcined at 390°C for 9 h under air atmosphere at a rate of 3°C / min to obtain catalyst powder. The general formula for the proportions of its elements is Mo. 12 V 4.4 W 1.8 Cu 1.5 Sb 1.3 O x It is denoted as STL-BM-5W-2.

[0069] Example 6: Mo 12 V 3.7 W 2.5 Cu 2.3 Sb 0.5 O x Preparation of -5wt%H2O (STL-BM-5W-3)

[0070] A method for preparing small-particle-size Mo-V-based catalysts using wet ball milling includes the following steps:

[0071] S1. Weigh out 55.0 g ammonium molybdate, 11.24 g ammonium metavanadate, 15.99 g ammonium metatungstate, 14.43 g copper nitrate and 3.88 g antimony acetate in sequence and add them to a conical mixer. Stir at 15 rpm / min for 10 min and then add 5.03 g hydroxyethyl cellulose. Continue stirring for 10 min.

[0072] S2. After mixing, transfer the mixture to a ball mill, add 5.03 g of water and 2.01 g of glycerol in sequence, and ball mill at 250 rpm / min for 20 min;

[0073] S3. After ball milling, dry in an oven at 80℃ for 2 h to obtain the catalyst precursor;

[0074] S4. The catalyst precursor was placed in a tube furnace and calcined at 390°C for 9 h under air atmosphere at a rate of 3°C / min to obtain catalyst powder. The general formula for the proportions of its elements is Mo. 12 V 3.7 W 2.5 Cu 2.3 Sb 0.5 O x It is denoted as STL-BM-5W-3.

[0075] Example 7: Mo 12 V4W 2.2 Cu2Sb 0.8 O xPreparation of -5wt%H2O-Oxi (STL-BM-5W-Oxi)

[0076] A method for preparing small-particle-size Mo-V-based catalysts using wet ball milling includes the following steps:

[0077] S1. Weigh out 3.2 g of molybdenum oxide, 11.24 g of ammonium metavanadate, 15.99 g of ammonium metatungstate, 3.89 g of copper sulfate and 3.03 g of antimony oxide in sequence and add them to a conical mixer. Stir at 15 rpm / min for 8 min and then add 1.82 g of hydroxyethyl cellulose. Continue stirring for another 8 min.

[0078] S2. After mixing, transfer the mixture to a ball mill, add 1.82 g of water and 0.73 g of glycerol in sequence, and ball mill at 300 rpm / min for 30 min;

[0079] S3. After ball milling, dry in an oven at 80℃ for 1 h to obtain the catalyst precursor;

[0080] S4. The catalyst precursor was placed in a tube furnace and calcined at 400°C for 11 h under air atmosphere at a rate of 3°C / min to obtain catalyst powder. The general formula for the proportions of its elements is Mo. 12 V4W 2.2 Cu2Sb 0.8 O x It is denoted as STL-BM-5W-3.

[0081] Comparative Example 1: Mo 12 V4W 2.2 Cu2Sb 0.8 O x Preparation of * (STL-BM-1)

[0082] Mo-V based catalysts were prepared by dry ball milling, without the addition of water, compared to Example 1.

[0083] Specifically, the steps include the following:

[0084] S1. Weigh out 55.0 g ammonium molybdate, 12.15 g ammonium metavanadate, 14.07 g ammonium metatungstate, 12.54 g copper nitrate and 6.21 g antimony acetate in sequence and add them to a conical mixer. Stir at 15 rpm / min for 10 min and then add 5.0 g hydroxyethyl cellulose. Continue stirring for 10 min.

[0085] S2. After mixing, transfer the mixture to a ball mill, add 2.0 g of glycerol, and ball mill at 250 rpm / min for 20 min;

[0086] S3. After ball milling, dry in an oven at 80℃ for 2 h to obtain the catalyst precursor;

[0087] S4. The catalyst precursor was placed in a tube furnace and calcined at 390°C for 9 h under air atmosphere at a rate of 3°C / min to obtain catalyst powder. The general formula for the proportions of its elements is Mo. 12 V4W 2.2 Cu2Sb 0.8 O x *, denoted as STL-BM-1.

[0088] Comparative Example 2: Mo 12 V4W 2.2 Cu2Sb 0.8 O x **Preparation (STL-BM-2)

[0089] A method for preparing small-particle-size Mo-V-based catalysts using wet ball milling, which, compared to Example 1, does not contain hydroxyethyl cellulose;

[0090] Specifically, the steps include the following:

[0091] S1. Weigh out 55.0 g ammonium molybdate, 12.15 g ammonium metavanadate, 14.07 g ammonium metatungstate, 12.54 g copper nitrate and 6.21 g antimony acetate in sequence and add them to a conical mixer. Stir at 15 rpm / min for 20 min.

[0092] S2. After mixing, transfer the mixture to a ball mill, add 5.00 g of water and 2.00 g of glycerol in sequence, and ball mill at 250 rpm / min for 20 min;

[0093] S3. After ball milling, dry in an oven at 80℃ for 2 h to obtain the catalyst precursor;

[0094] S4. The catalyst precursor was placed in a tube furnace and calcined at 390°C for 9 h under air atmosphere at a rate of 3°C / min to obtain catalyst powder. The general formula for the proportions of its elements is Mo. 12 V4W 2.2 Cu2Sb 0.8 O x **, denoted as STL-BM-2.

[0095] Comparative Example 3: Mo 12 V4W 2.2 Cu2Sb 0.8 O x Preparation of *** (STL-BM-3)

[0096] The Mo-V based catalyst prepared by dry ball milling is free of water, hydroxyethyl cellulose and glycerol compared with Example 1;

[0097] Specifically, the steps include the following:

[0098] S1. Weigh out 55.0 g ammonium molybdate, 12.15 g ammonium metavanadate, 14.07 g ammonium metatungstate, 12.54 g copper nitrate and 6.21 g antimony acetate in sequence and add them to a conical mixer. Stir at 15 rpm / min for 20 min.

[0099] S2. After mixing, transfer the mixture to a ball mill and ball mill at a rate of 250 rpm / min for 20 min;

[0100] S3. After ball milling, dry in an oven at 80℃ for 2 h to obtain the catalyst precursor;

[0101] S4. The catalyst precursor was placed in a tube furnace and calcined at 390°C for 9 h under air atmosphere at a rate of 3°C / min to obtain catalyst powder. The general formula for the proportions of its elements is Mo. 12 V4W 2.2 Cu2Sb 0.8 O x ***, denoted as STL-BM-3. Its XRD pattern and SEM image are as follows: Figure 1 and Figure 4 As shown.

[0102] Comparative Example 4: Mo 12 V4W 2.2 Cu2Sb 0.8 O x Preparation of -5wt%H2O (STL-BM-5W-4)

[0103] A method for preparing small-particle-size Mo-V-based catalysts using wet ball milling, compared with Example 1:

[0104] In step S2, the ball milling rate was adjusted to 180 rpm / min, and the ball milling time was adjusted to 40 min. Its XRD pattern is shown below. Figure 2 As shown.

[0105] Comparative Example 5: Mo 12 V4W 2.2 Cu2Sb 0.8 O x Preparation of -5wt%H2O (STL-BM-5W-5)

[0106] A method for preparing small-particle-size Mo-V-based catalysts using wet ball milling, compared with Example 1:

[0107] In step S4, the calcination temperature was adjusted to 300℃ and the time to 24 h. Its XRD pattern is shown below. Figure 2 As shown.

[0108] Comparative Example 6: Mo 12 V4W 2.2 Cu2Sb 0.8 O x Preparation of -5wt%H2O (STL-BM-5W-6)

[0109] A method for preparing small-particle-size Mo-V-based catalysts using wet ball milling, compared with Example 1:

[0110] In step S4, the calcination temperature was adjusted to 430℃ and the time to 8 hours. Its XRD pattern is shown below. Figure 2 As shown.

[0111] Comparative Example 7: Mo 12 V4W 2.2 Cu2Sb 0.8 O x Preparation of -HS (STL-HS)

[0112] The hydrothermal preparation of Mo-V based catalysts specifically includes the following steps:

[0113] S1. Heat 500 mL of deionized water to 95℃, add 55.00 g ammonium molybdate, 12.15 g ammonium metavanadate and 14.07 g ammonium metatungstate in sequence and stir continuously for 30 min. Then add 12.54 g copper nitrate and 6.21 g antimony triacetate in sequence and continue stirring for 4 h to obtain a uniform aqueous slurry.

[0114] S2. After the above aqueous slurry is cooled to 40°C, it is placed in a tray and dried continuously in an oven at 90°C for 24 hours to obtain a black catalyst precursor. The blocky precursor is then ground and pulverized to obtain a uniform powder.

[0115] S3. The above powder was transferred to a ceramic boat and placed in a tube furnace. It was continuously calcined at 390°C for 9 h under conditions of an air flow rate of 30 mL / min and a heating rate of 2°C / min, to obtain the catalyst active powder. The general formula for the proportions of its elements is Mo. 12 V4W 2.2 Cu2Sb 0.8 O x It is denoted as STL-HS. Its XRD pattern and SEM image are as follows: Figure 1 and Figure 5 As shown.

[0116] Performance testing

[0117] 1. Catalyst performance evaluation

[0118] Catalyst performance evaluation experiments were conducted in a two-stage fixed-bed reaction tube. The first stage fixed bed used the same catalyst and conditions for in-situ generation of acrolein, while the second stage fixed bed was used to test the catalysts prepared in Examples 1-7 and Comparative Examples 1-7.

[0119] Specific reaction conditions: First, the catalysts prepared in Examples 1-7 and Comparative Examples 1-7 were tableted, pulverized, and sieved to form catalyst particles of 20-60 mesh. 20 g of catalyst particles and 20 g of quartz sand of the same mesh size were mixed and loaded into a fixed-bed reactor. The ratios of propylene / water / air1 / nitrogen / air2 were 1 / 1.00 / 8.13 / 2.40 / 2.39, and the propylene space velocity in the first stage of the fixed bed was 90 h⁻¹. -1 The catalyst performance was tested under the following conditions: propylene concentration 8.0%, inlet pressure 40 kPa, temperature 330℃; two-stage fixed bed outlet pressure 20 kPa, reaction temperature 260℃. The catalyst activity data was analyzed using gas chromatography. The specific results are shown in Table 1 below.

[0120] Table 1. Comparison of catalytic performance between Examples 1-7 and Comparative Examples 1-7

[0121]

[0122] As shown in Table 1, Examples 1, 2, Comparative Examples 1 and 3, the acrolein conversion rate of the catalyst prepared by dry ball milling (Comparative Examples 1 and 3) was less than 60%. Adding a small amount of water (1 wt%) increased the acrolein conversion rate to over 95% (Comparative Example 2). When the water content reached 5 wt% (Example 1), the acrolein conversion rate was 99.9%, the acrylic acid selectivity was 93.6%, and the acrylic acid yield reached 93.6%. Compared with the traditional hydrothermal method (Comparative Example 7), the acrylic acid selectivity increased by 2.4%, leading to a simultaneous increase in acrylic acid yield. Figure 1 It can be seen that the catalyst crystal structure in the dry ball milling method contains a large amount of MoO3, while the crystal structure of the catalyst in the wet ball milling method is similar to that of the traditional hydrothermal method. The SEM mapping diagram of the catalyst obtained in Example 1 shows that each element is uniformly distributed on the catalyst surface, indicating that adding a small amount of water in the ball milling method helps to generate the active phase.

[0123] As shown in Table 1, Examples 1 and Comparative Examples 4-6, reducing the ball milling rate to 180 rpm / min decreased the acrolein conversion rate of the catalyst to 86.7%, indicating that at low ball milling rates, the probability of collisions between raw materials decreases, leading to hindered formation of the active phase and reduced catalytic activity. Figure 2Lowering the calcination temperature to 300℃ or raising it to 450℃ resulted in a decrease in propylene conversion of the catalyst to below 60%, indicating that a suitable calcination temperature is beneficial for the growth of the target crystalline phase. Too low a temperature prevents the formation of an effective target crystalline phase, while too high a temperature leads to crystalline phase collapse and deformation, resulting in reduced catalyst activity. Figure 2 ).

[0124] 2. Evaluation of catalyst physical properties

[0125] Table 2 Comparison of particle size and specific surface area between Examples 1-7 and Comparative Examples 3 and 7

[0126]

[0127] BET and particle size analyses in Table 2 revealed that the specific surface area of ​​the catalyst obtained by wet ball milling ranged from 7.01 to 8.99 m². 2 The catalyst in Comparative Example 7, prepared by a conventional hydrothermal method, has a specific surface area of ​​6.71 m² / g, with a pore size of 10.45–12.33 nm and a pore volume of 0.036–0.048 cc / g. The particle size distribution shows a D50 of 0.46–0.64 μm and a D90 of 10.20–13.56 μm. 2 The catalyst has a particle size distribution of / g, a pore size of 10.23 nm, and a particle size distribution of D50 = 5.71 μm and D90 = 27.27 μm. The above characterization reveals that adding a pore-forming agent during wet ball milling can effectively increase the specific surface area and pore size of the catalyst; simultaneously, the high-speed rotating grinding beads can effectively reduce the particle size of the catalyst, resulting in Example 1 exhibiting higher acrylic acid selectivity compared to Comparative Example 4.

[0128] Furthermore, Examples 1-4 show that the catalyst exhibits optimal activity when the water content is increased to 5 wt%. When the water content is greater than 5 wt%, the water content during the preparation process has little effect on the acrolein conversion rate of the catalyst, mainly affecting the selectivity of acrylic acid. The higher the water content, the lower the selectivity of acrylic acid and the lower the yield of acrylic acid, but all can remain above 90%. Examples 1 and 5-7 show that, under suitable formulations, the wet ball milling method has universality. After the catalyst raw material becomes an oxide, its activity decreases to some extent due to its greater stability.

[0129] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing small-particle-size Mo-V-based catalysts using wet ball milling, characterized in that, Includes the following steps: (1) Place the raw materials containing Mo, V, W, Cu, and Sb and the pore-forming agent into a mixer, mix them, and then transfer them to a ball mill jar to obtain a mixture; (2) Add lubricant and water to the mixture; the amount of water added is 1-15 wt% of the total mass of the raw materials containing Mo, V, W, Cu, and Sb. (3) At normal temperature and pressure, the ball mill jar is used to ball mill for 10-40 min at a rate of 150-400 rpm / min; (4) After ball milling, the mixture is dried in an oven to obtain the catalyst precursor; (5) The catalyst precursor was placed in a tube furnace and calcined to obtain a small particle size Mo-V-based catalyst.

2. The method according to claim 1, characterized in that, The Mo-containing raw material is selected from at least one of ammonium molybdate and molybdenum trioxide; The raw material containing V is selected from at least one of vanadium oxalate, ammonium metavanadate, and vanadium pentoxide; The raw material containing W is selected from at least one of ammonium tungstate, ammonium paratungstate, ammonium metatungstate, and tungsten trioxide; The raw materials containing Cu are selected from at least one of copper carbonate, copper nitrate, copper sulfate, basic copper sulfate, copper acetate, copper oxalate, copper phosphate, and copper oxide. The raw materials containing Sb are selected from at least one of antimony acetate and antimony oxide.

3. The method according to claim 1, characterized in that, The pore-forming agent is selected from at least one of carboxymethyl cellulose, hydroxyethyl cellulose, polyoxyethylene polyoxypropylene ether block copolymer, polyethylene oxide-polyoxypropylene-polyoxyethylene triblock copolymer, and polyethylene glycol, and its addition amount is 2 to 10 wt% of the total mass of the raw materials containing Mo, V, W, Cu, and Sb.

4. The method according to claim 1, characterized in that, The lubricant is selected from at least one of glycerol, ethanolamine, and ethylene glycol, and its addition amount is 0 to 5 wt% of the total mass of raw materials containing Mo, V, W, Cu, and Sb.

5. The method according to claim 1, characterized in that, The ball milling jar is used to ball mill for 15-30 minutes at a speed of 200-300 rpm / min.

6. The method according to claim 1, characterized in that, The air feed rate of the tubular furnace is 10-40 mL / min, and the heating rate is 2-4℃ / min.

7. The method according to claim 1, characterized in that, The roasting temperature is 330~410℃, and the time is 8~12 hours.

8. A small-particle-size Mo-V-based catalyst prepared by wet ball milling, characterized in that, Obtained by the method according to any one of claims 1-7, its general formula is Mo 12 V a W b Cu c Sb d O x In the formula, a, b, c, and d represent the atomic ratios of each element, where a = 1~5, b = 0.5~2.5, c = 0.5~3, and d = 0~1.

5.

9. The small-particle-size Mo-V-based catalyst according to claim 8, characterized in that, The catalyst has a particle size D50 of 0.46-0.64 μm, a D90 of 10.20-13.56 μm, and a specific surface area of ​​7.01-8.99 m². 2 / g.

10. The application of a small-particle-size Mo-V-based catalyst prepared by wet ball milling as described in claim 8, characterized in that, It is used in the catalytic oxidation of acrolein to prepare acrylic acid.

Citation Information

Patent Citations

  • Oxide catalyst, process for producing acrolein or acrylic acid and process for producing water-absorbent resin

    CN101274279B

  • A process for producing acrylic acid

    CN101328116B

  • Preparation method of catalyst for acrylic acid by oxidizing acraldehyde

    CN102039143B

  • Method for preparing catalyst in preparation of acrylic acid by oxidizing acrolein

    CN102114427B

  • Catalyst for oxidation of acrolein and process for preparation thereof

    CN1031488A